Issues with the Speaking Section of the International English Language Testing System (IELTS): An Assessment Critique - Solihin Solihin; Aprianti Ari Dwi Intan; Utami Dita Rezkia; Sari Mayang (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The International English Language Testing System (IELTS) is one of the most widely used tests of English internationally. It is a testing system designed or owned by three partners: University of Cambridge ESOL Examination, British Council, and IDP Australia. This research is to critique the speaking section of the IELTS based on the experience of some test-takers involved as the subjects of this research. The method used was descriptive qualitative. Data collection techniques applied were content analysis, interview, and self -reflection. Two IELTS test-takers were interviewed to get their views on the three phases of the speaking section. The authors’ own experiences when taking the IELTS were also reported.  It was found that there are issues with the speaking section of the IELTS. Those issues are its: fairness, authenticity, validity, and the appropriateness of interview as a sole tool to assess speaking ability. This paper also suggests a number of actions to be taken in order to make the speaking section fair, authentic, and valid. Additionally, other ways of assessing speaking ability are proposed.  This paper then reveals what these issues mean to test-takers, examiners, and organizations running IELTS.